VARIASI BAHASA DAYAK BI SOMU DI KABUPATEN SANGGAU - Apriyani, Fitri; Patriantoro; Mellisa Jupitasari (Universitas Tanjungpura, 2026)
This study aims to determine the language variations found in the Dayak Bi Somu language in Sanggau Regency, precisely in three villages in three sub-districts, namely Idas village in Noyan District, Mobui village in Kembayan District, and Sungai Ilai village in Beduai District. The method used is quantitative descriptive method, becaʊse in determining the difference in language variation, dialectometric calculations are used to get a percentage in the study so that it can be described according to the calculation results. The data obtained in this study are direct speech by speakers from three observation points in Sanggau Regency. The data can be in the form of Dayak Bi Somu language in the form of swades words. Based on the results of the study, 106 lexical variations were found from 513 lists of questions asked in the Dayak Bi Somu language at three observation points. There are 106 maps containing lexical data. The map contains lexical data with a symbol system. Based on the results of dialectometric calculations, the percentage found ranged from 4.48% - 20.66%